New Species of Entypus (Hymenoptera: Pompilidae) and notes on the natural history of some Atlantic Forest spider wasps - Lopez, Vinicius M.; DE Oliveira Alves Cardoso, Renan Kobal; Cezrio, Rodrigo R.; Guillermo-Ferreira, Rhainer; Santos, Eduardo F Dos [UNESP] (Magnolia Press, 2021)
We describe the new species Entypus renata, sp. nov., from the Brazilian Atlantic Forest and report on its host. We also provide the first host records for Ageniella (Priophanes) erythroptera (Banks), Entypus bituberculatus (Gurin-Meville) and an undetermined species of Poecilopompilus Ashmead. In addition, we report behavioral aspects for these species, including a new ethological sequence for Poecilopompilus.